Nimodipine enhances neurite outgrowth in dopaminergic brain slice co‐cultures. Issue 40 (4th November 2014) - Sygnecka, Katja; Heine, Claudia; Scherf, Nico; Fasold, Mario; Binder, Hans; Scheller, Christian; Franke, Heike
Abstract: Calcium ions (Ca 2+ ) play important roles in neuroplasticity and the regeneration of nerves. Intracellular Ca 2+ concentrations are regulated by Ca 2+ channels, among them L‐type voltage‐gated Ca 2+ channels, which are inhibited by dihydropyridines like nimodipine. The purpose of this study was to investigate the effect of nimodipine on neurite growth during development and regeneration. As an appropriate model to study neurite growth, we chose organotypic brain slice co‐cultures of the mesocortical dopaminergic projection system, consisting of the ventral tegmental area/substantia nigra and the prefrontal cortex from neonatal rat brains. Quantification of the density of the newly built neurites in the border region (region between the two cultivated slices) of the co‐cultures revealed a growth promoting effect of nimodipine at concentrations of 0.1 μM and 1 μM that was even more pronounced than the effect of the growth factor NGF. This beneficial effect was absent when 10 μM nimodipine were applied. Toxicological tests revealed that the application of nimodipine at this higher concentration slightly induced caspase 3 activation in the cortical part of the co‐cultures, but did neither affect the amount of lactate dehydrogenase release or propidium iodide uptake nor the ratio of bax/bcl‐2. Furthermore, the expression levels of different genes were quantified after nimodipine treatment. The expression of Ca 2+ binding proteins, immediate early genes, glial fibrillary acidic protein, and myelin components did not change significantly after treatment, indicating that the regulation of their expression is not primarily involved in the observed nimodipine mediated neurite growth. In summary, this study revealed for the first time a neurite growth promoting effect of nimodipine in the mesocortical dopaminergic projection system that is highly dependent on the applied concentrations.